2018
DOI: 10.1039/c8fo00526e
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids fromZiziphus jujubainduce apoptotic cell death in human cancer cells through mitochondrial reactive oxygen species production

Abstract: Ziziphus jujuba var. inermis Rehder is an edible fruit-producing species of the Rhamnaceae family. In the present study, we isolated eight triterpenoids (1-8) from the fruits of Z. jujuba var. inermis and evaluated their apoptotic cell-death-inducing activities in human cancer cell lines (A549, PC-3, and MDA-MB-231). The structures of compounds 1-8 were determined by spectroscopic methods. Among these, four isomers of coumaroyl alphitolic acid showed potent cytotoxic activities on these cancer cells: 3-O-cis-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The dried fruits and seeds of jujubes are also valued as a traditional herbal medicine in Asian countries (Liu, 2008). Recently, a series of studies revealed that fruit extracts of jujube induced apoptotic cell death in human cancer cells (Abedini et al ., 2016; Shin et al ., 2018; Sun et al ., 2013), suggesting jujube may be a promising agent to prevent or treat human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The dried fruits and seeds of jujubes are also valued as a traditional herbal medicine in Asian countries (Liu, 2008). Recently, a series of studies revealed that fruit extracts of jujube induced apoptotic cell death in human cancer cells (Abedini et al ., 2016; Shin et al ., 2018; Sun et al ., 2013), suggesting jujube may be a promising agent to prevent or treat human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Among these substances, polyphenols from jujube, secondary metabolites of plants, are important determinants of the nutritional and organoleptic qualities of Zizyphus lotus [21,22]. Several bioactive compounds extracted from jujubes have attracted the attention of many researchers due to their important biological actions, including antioxidant [19,23], enzyme inhibitory [24,25], antiproliferative and cytotoxic effects [24,26], anti-inflammatory, and other effects [27][28][29], which can be used in the food, pharmaceutical, and cosmetic industry.…”
Section: Introductionmentioning
confidence: 99%
“…), also known as the Chinese date, is an important fruit tree (2n = 2x = 24) in the family of Rhamnaceae. The fruit active ingredient of Chinese jujube has recently been affirmed to possess strong anti-cancer activity [14,15], and is especially rich in ascorbic acid, flavonoid, amino acids, mineral constituents, cerebrosides, and cyclic adenosine monophosphate [16], in addition to carbohydrates, making it highly valuable in both nutrition and medication. It has been cultivated in China for up to 7,000 years, and has been introduced to 47 countries throughout the Americas, southern and eastern Asia, Europe, and Australia [17].…”
Section: Introductionmentioning
confidence: 99%